Computer Vision and Machine Learning for Intelligent Sensing Systems - Tian, Jing (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The reprint offers a selection of high-quality research articles that tackle the major difficulties in computer vision and machine learning for intelligent sensing systems from both theoretical and practical standpoints. This publication includes intelligent sensing techniques, twelve foundational investigations into sense-making methods, and discusses particular uses of intelligent sensing systems in autonomous driving and virtual reality.